2021
DOI: 10.1038/s41467-021-26270-3
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing cancer drugs identifies kenpaullone which ameliorates pathologic pain in preclinical models via normalization of inhibitory neurotransmission

Abstract: Inhibitory GABA-ergic neurotransmission is fundamental for the adult vertebrate central nervous system and requires low chloride concentration in neurons, maintained by KCC2, a neuroprotective ion transporter that extrudes intracellular neuronal chloride. To identify Kcc2 gene expression‑enhancing compounds, we screened 1057 cell growth-regulating compounds in cultured primary cortical neurons. We identified kenpaullone (KP), which enhanced Kcc2/KCC2 expression and function in cultured rodent and human neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 99 publications
1
34
0
Order By: Relevance
“…Firstly, we found that the chloride equilibrium potential ( E Cl - ) in pSNL mice was significantly shifted to a more positive value by using whole-cell patch-clamp technique, indicating an elevated level of [Cl − ] i in pSNL animals. The result was consistent with the previous finding that neuronal intracellular chloride concentration was increased in the superficial dorsal horn after nerve injury ( Yeo et al, 2021 ). Only 3-days continuous intrathecal infusion, but not a short-term incubation of OT, restored the value of E Cl - , suggesting that only continuous intrathecal OT infusion was able to restore [Cl − ] i .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Firstly, we found that the chloride equilibrium potential ( E Cl - ) in pSNL mice was significantly shifted to a more positive value by using whole-cell patch-clamp technique, indicating an elevated level of [Cl − ] i in pSNL animals. The result was consistent with the previous finding that neuronal intracellular chloride concentration was increased in the superficial dorsal horn after nerve injury ( Yeo et al, 2021 ). Only 3-days continuous intrathecal infusion, but not a short-term incubation of OT, restored the value of E Cl - , suggesting that only continuous intrathecal OT infusion was able to restore [Cl − ] i .…”
Section: Discussionsupporting
confidence: 93%
“…It was reported that neuronal intracellular chloride concentration was increased in the superficial dorsal horn after nerve injury ( Yeo et al, 2021 ), we performed perforated patch-clamp recording in spinal cord slices derived from each group to investigate the effects of OT on chloride homeostasis ( Figure 3A ). Since GABA A receptor (GABA A R) is the dominant chloride ion channel on the membrane of neurons in the superficial dorsal horn, GABA was puffed briefly to the recorded neuron to trigger transient chloride influx or efflux.…”
Section: Resultsmentioning
confidence: 99%
“…The conflicting evidence regarding the involvement of GSK3 in HD likely stem from the opposing actions of the different GSK3 isoforms (D'Mello, 2021). GS3Kβ phosphorylates Thr906-KCC2 and KCC2 activity (Watanabe et al, 2019), and inhibition of GSK3β enhances KCC2 expression and restores E GABA in a model of nerveinjury pain (Yeo et al, 2021). The potential effects of altered GSK3 activity on KCC2 activity in HD remains to be determined but offers an interesting and important avenue for exploration.…”
Section: D1-and D2-msns Differential Vulnerability In Huntington's Di...mentioning
confidence: 99%
“…Further evidence that targeting ionic plasticity has therapeutic potential in the treatment of neuropathic pain was provided by Yeo and colleagues [ 114 ]. A drug screen identified kenpaullone, a cancer therapeutic, that augments KCC2.…”
Section: Painmentioning
confidence: 99%